2018
DOI: 10.1016/j.clml.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

VcR-CVAD Induction Chemotherapy Followed by Maintenance Rituximab Produces Durable Remissions in Mantle Cell Lymphoma: A Wisconsin Oncology Network Study

Abstract: Introduction VcR-CVAD was developed as an intermediate-intensity induction regimen with maintenance rituximab (MR) to improve remission durations after first-line therapy for mantle cell lymphoma (MCL) in older and younger MCL patients. Patients and Methods Patients with previously untreated MCL received VcR-CVAD induction chemotherapy for 6 cycles (21-day cycles). Patients achieving at least a partial response received rituximab consolidation (375 mg/m2 × 4 weekly doses) and MR (375 mg/m2 every 12 weeks × 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Treatment broadly consists of two components: cytarabine-containing induction chemotherapy followed by ASCT. Phase II trials in the past decade have consistently demonstrated the impressive activity of cytarabine in MCL, namely in the Hyper-CVAD and VcR-CVAD regimens 11 13 . Since that time, the MCL Younger trial conducted by the European MCL Network provided phase III data to support cytarabine as the key agent in MCL induction 14 .…”
Section: Treatment Strategies In Fit Patientsmentioning
confidence: 99%
“…Treatment broadly consists of two components: cytarabine-containing induction chemotherapy followed by ASCT. Phase II trials in the past decade have consistently demonstrated the impressive activity of cytarabine in MCL, namely in the Hyper-CVAD and VcR-CVAD regimens 11 13 . Since that time, the MCL Younger trial conducted by the European MCL Network provided phase III data to support cytarabine as the key agent in MCL induction 14 .…”
Section: Treatment Strategies In Fit Patientsmentioning
confidence: 99%
“…This regimen showed improved results with an ORR of 90% and a CRR of 77%. The 6-year PFS and OS were 53 and 70% respectively, and there was no difference of 6-year PFS and OS between the age subgroups (age < 60 years and age ≥ 60 years) [ 27 ].…”
Section: Trials For Older Patientsmentioning
confidence: 99%
“…However, the response rates and PFS seen with the SCR regimen compare favourably with other less intensive induction regimens. For example, the CR rate with SCR was higher than that seen in prospective studies using BR (40%), R‐cladribine (52%), R‐CHOP (34–42%), and VR‐CAP (rituximab, cyclophosphamide, doxorubicin and prednisone plus bortezomib; 53%) (Kluin‐Nelemans et al , ; Robak et al , ; Chen et al , ; Le Gouill et al , ; Visco et al , ; Chang et al , ; Ruan et al , ; Tam et al , ). Furthermore, although MRD testing was only available for 14 responding patients, all were MRD‐negative after induction.…”
Section: Discussionmentioning
confidence: 95%
“…Improvement in outcomes is particularly notable for mantle cell lymphoma (MCL); however, relapse and death remain the norm (Schmidt & Dreyling, ; Herrmann et al , ; Chandran et al , ) and much of the progress seen to date has been demonstrated in younger patients (age <60–65 years) who are eligible for aggressive treatment (LaCasce et al , ). Despite recent advances, it remains unknown if less intense therapy is inferior to aggressive treatment and poor risk patients continue to have poor outcomes (Kluin‐Nelemans et al , ; Robak et al , ; Le Gouill et al , ; Visco et al , ; Chang et al , ; Obr et al , ; Ruan et al , ; Tam et al , ). Identifying treatment strategies that incorporate novel therapeutic approaches irrespective of patient age remains a high priority.…”
mentioning
confidence: 99%